2020
DOI: 10.1088/1361-6633/abaa39
|View full text |Cite
|
Sign up to set email alerts
|

Review: knots and other new topological effects in liquid crystals and colloids

Abstract: Humankind has been obsessed with knots in religion, culture and daily life for millennia, while physicists like Gauss, Kelvin and Maxwell already involved them in models centuries ago. Nowadays, colloidal particles can be fabricated to have shapes of knots and links with arbitrary complexity. In liquid crystals, closed loops of singular vortex lines can be knotted by using colloidal particles and laser tweezers, as well as by confining nematic fluids into micrometer-sized droplets with complex topology. Knotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 238 publications
2
69
0
Order By: Relevance
“…A spherical glycerol droplet has a genus equal to zero and Euler characteristic χ Euler = 2. Consistent with topological theorems ( 2 , 3 , 13 , 22 , 23 ), the hedgehog charge of the three-dimensional topological defects π 2 ( 2 /ℤ 2 ) = ℤ induced in the nematic LC bulk [the hyperbolic hedgehog point defect and the equivalent to it Saturn ring of π 1 ( 2 /ℤ 2 ) = ℤ 2 disclination] that compensates the hedgehog charge of surface boundary conditions at the drop surface is equal ±χ Euler /2 = ±1; the sign of the induced defect can be determined upon decorating the nonpolar director field with a unit vector field along one of the two antiparallel directions ( 23 , 40 ). The net winding number of π 1 ( 1 ) LC defects in the two-dimensional interfacial director field at the LC-glycerol interface is equal to χ Euler = 2, with the two boojums each having a winding of unity [ Figs.…”
Section: Resultsmentioning
confidence: 99%
“…A spherical glycerol droplet has a genus equal to zero and Euler characteristic χ Euler = 2. Consistent with topological theorems ( 2 , 3 , 13 , 22 , 23 ), the hedgehog charge of the three-dimensional topological defects π 2 ( 2 /ℤ 2 ) = ℤ induced in the nematic LC bulk [the hyperbolic hedgehog point defect and the equivalent to it Saturn ring of π 1 ( 2 /ℤ 2 ) = ℤ 2 disclination] that compensates the hedgehog charge of surface boundary conditions at the drop surface is equal ±χ Euler /2 = ±1; the sign of the induced defect can be determined upon decorating the nonpolar director field with a unit vector field along one of the two antiparallel directions ( 23 , 40 ). The net winding number of π 1 ( 1 ) LC defects in the two-dimensional interfacial director field at the LC-glycerol interface is equal to χ Euler = 2, with the two boojums each having a winding of unity [ Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TDs could efficiently trap appropriate nanoparticles [31,32]. Note that TDs in liquid crystals could be relatively easily manipulated [33][34][35][36][37][38][39][40][41], which offers an indirect path to manipulate assemblies of trapped NPs. Finally, understanding the curvature-enabled stabilization mechanisms of TDs and their assemblies might shed light on still unresolved problems in fundamental physics [42].…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] Several consequent studies revealed that similar structures appear also in LCs. [ 53–58 ] Such structures are referred to as “textures” and are also characterized by conserved topological numbers. However, they are not singular in the respective physical field.…”
Section: Discussionmentioning
confidence: 99%